Safer and more efficient vital signs monitoring to identify the deteriorating patient: an observational study towards deriving evidence-based protocols for patient surveillance on the general hospital ward - Briggs, J; Kostakis, I; Meredith, P; Darbyshire, J; Gerry, S; Watkinson, P; Redfern, O (NIHR Journals Library, 2024)
Background